APPLICATION OF EXERGOECONOMIC ANALYSIS FOR POWER PLANTS - Unal, Fatih; Ozkan, Derya Burcu (VINCA INST NUCLEAR SCI, 2018)
Currently, energy resources are rapidly consumed. Therefore, scientists and engineers study the effective use of energy. In the present study, a thermodynamic and exergoeconomic analysis was performed in a thermal power plant in Turkey. The study involved determining the thermodynamic properties of 27 node points in a thermal power plant unit, and this was followed by calculating energy and exergy values of every node. Mean exergy costs were calculated by establishing energy and exergy balances of the equipment with respect to the calculated results. Subsequently, lost and damaged energies and exergies were calculated, and exergoeconomic factors were determined. The equipments were compared with each other on a graph based on the obtained results. The maximum rate of exergy loss and cost of exergy destruction corresponded to 79.5% and 886,66 $/h, respectively. The maximum exergy losses in a thermal power plant occurred in the boiler, turbine groups, condenser, heating group, pumps, and auxiliary groups. The highest and second highest law efficiencies of the studied thermal power plant corresponded to 32.3% and 28.5%, respectively. The study also involved presenting suggestions for improvement. Additionally, exergoeconomic analyses were conducted while considering the power plants' investment and equipment maintenance costs. It is expected that the calculation method and the obtained results can be applied to other thermal power plants.
Keywords: exergoeconomic analysis; thermal power plant; exergy analysis; thermodynamic analysis; THERMOECONOMIC ANALYSIS; ENERGY; Thermodynamics